2020
DOI: 10.2147/cmar.s253174
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of circRNA_0000285 Suppresses Cervical Cancer Development by Regulating miR197-3p–ELK1 Axis</p>

Abstract: Background Circular RNAs (circRNAs) are involved in the development of human cancers, including cervical cancer (CC). However, the role and mechanism of the circRNA hsa_circ_0000285 ( circ_0000285 ) in CC development remain largely unknown. Methods Thirty paired CC and adjacent normal tissue samples were harvested. CC cell lines SiHa and HeLa were cultured in this study. The expression of circ_0000285 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Previous studies have reported that circRNAs are involved in cancer development by regulating the expression of specific target genes ( 8 , 11 ). Initially, bioinformatics analysis was performed to predict the target gene of circRNA_0000285.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that circRNAs are involved in cancer development by regulating the expression of specific target genes ( 8 , 11 ). Initially, bioinformatics analysis was performed to predict the target gene of circRNA_0000285.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that circRNAs contain several miRNA binding sites, which are involved in the regulation of gene expressions by sponging miRNAs ( 9 , 10 ). circRNA_0000285 has been identified as a novel circRNA, which promotes the metastasis and invasion of several types of cancer by targeting specific miRNAs ( 11 ). However, the roles and underlying molecular mechanism of circRNA_0000285 in thyroid cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is currently theorized that circRNAs are mainly distributed in the cytoplasm and play a role in regulating tumor progression through the adsorption of miRNAs. For example, circ_0001785 can sponge miR-942 or miR-1200 to regulate breast cancer or osteosarcoma progression, respectively ( 31 , 32 ); and circ_0000285 can absorb miR-409-3p, miR-197-3p and miR-599, thereby affecting the progression of cervical cancer and osteosarcoma ( 24 , 33 , 34 ). Analysis using an online database revealed 29 miRNAs that may serve as the target of circ_0001367.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ELK1, ETV4, STAT3 and TFAP2A were signi cant TFs, which interacted with the hub genes. TF ELK1 has been found to act a carcinogenic role in human cancers, like hepatocellular carcinoma, thyroid cancer, breast cancer [67]. Jennifer T Cairns etal.…”
Section: Discussionmentioning
confidence: 99%